PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS 4 DALAM MATERI PECAHAN PADA MATA PELAJARAN MATEMATIKA DI SDN MERUYA SELATAN 03 PAGI - Nisa, Arba'atun; Pranata, Khavisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to investigate the effect of Problem Based Learning (PBL) on the mathematical communication skills of fourth-grade students in the topic of fractions at SDN Meruya Selatan 03 Pagi. The background of the study highlights students' common difficulties in expressing and understanding mathematical concepts, particularly in fractions, due to conventional teaching methods. To address this issue, the study implemented the PBL model, which emphasizes student-centered learning through real-world problem solving, collaboration, and active discussion. The research used a quasi-experimental design with two groups: an experimental group taught using PBL and a control group taught conventionally. Data were collected through pretest and posttest assessments using essay-type written tests that measured mathematical communication skills. The sample consisted of 64 students, divided equally between the two groups. Data analysis included N-Gain calculation, normality and homogeneity tests, and hypothesis testing using the t-test. The results revealed that students in the experimental group achieved a higher N-Gain score (0.55 moderate to high category) compared to the control group (0.23 low category). These findings suggest that the PBL model significantly enhances students' ability to communicate mathematical ideas orally and in writing, understand visual representations, and relate mathematical concepts to real-life situations. Therefore, PBL is recommended as an effective instructional model to improve mathematical communication skills in primary education, especially in the context of teaching fractions.